Infundibulicybe swatica (Basidiomycota, Agaricales), a new species from Pakistan - Kiran, Munazza; Amjad, Atika; Naseer, Arooj; Ullah, Zia; Razzaq, Annum; Hussain, Shah; Khalid, Abdul Nasir (Phytotaxa, 2024)
A new species, Infundibulicybe swatica is described and illustrated from District Swat, Khyber Pakhtunkhwa, Pakistan. The new taxon is characterized by pale yellow to pale yellow brown to brown pileus with a dark brown center; a bicolorous stipe, white at the apex and pale yellow brown hues at the base; hyaline, lacrymoid to sub-lacrymoid, small, inamyloid basidiospores (6.5 × 4.2 µm); and the absence of hymenial cystidia. Molecular phylogenetic analyses based on nuclear ribosomal Internal Transcribed Spacer (ITS) and nuclear ribosomal Large Subunit (LSU) regions confirm the novelty of the taxon.